Stroke epidemiology and stroke policies in China from 1980 to 2017: A systematic review and meta-analysis. Issue 1 (January 2020) - Hu, Sophia; Cui, Bijun; Mlynash, Michael; Zhang, Xin; Mehta, Kala M; Lansberg, Maarten G
Background: Stroke is the leading cause of death and years of life lost in China, and this problem is growing because stroke risk factors such as hypertension and hypercholesteremia have been on the rise as China experiences the demographic transition. The Chinese government has created public health initiatives in the form of guidelines, policies and programs to combat this problem, but the dissemination and effectiveness of these policies are not well known. Aims: The aim of this study was to determine trends in stroke incidence, prevalence, and stroke-related mortality in China and to report these trends in the context of stroke initiatives that have been enacted by the Chinese government. Summary of review: We systematically reviewed articles on stroke rates and stroke initiatives from 1980 to 2017. A meta-regression including 11 studies showed that stroke incidence remained stable at 128.3 per 100, 000 per year from 1980 to 2005 and has increased by 21.3 per 100, 000 per year since then to 298.7 per 100, 000 per year in 2013. A meta-regression including seven studies demonstrated a gradual decline in stroke-related mortality by 6.5 per 100, 000 per year since 1980 (a decline from 369.2 in 1980 to 154.7 per 100, 000 per year in 2013). Average stroke prevalence was 898.4 per 100, 000 over the entire time-period. Limitations included heterogeneity between the studies. We identified 12 stroke initiatives, the first of which was enacted in 2006. Conclusions: Despite numerous public health initiatives aimed at combating stroke that started in 2006, stroke incidence in China has increased over the last decade, likely as a result of aging and urbanization of the Chinese population.